The Effect of Brassica Oleracea (Cabbage) on The Pharmacokinetics of Ciprofloxacin in an Animal Model - Sa`adeh, Amani; Aburjai, Talal; Shraim, Nasr; Al-Ghazawi, Mutasim (Jordan Journal of Pharmaceutical Sciences, 2020)
The effect of Brassica oleracea (Cabbage) on the pharmacokinetics of ciprofloxacin was studied in rabbits. A single dose of Ciprofloxacin (40mg/kg) was given to rabbits as a suspension along with an aqueous extract of Brassica oleracea (var. capitata) equivalent to 2g/kg. Twelve rabbits were sampled in a two-period, two-sequence, crossover study, with 7day washout period. Blood samples were obtained at (t = 0, 5, 15, 25, 40, 60, 90, 120, 180, 240, 360, 480 and 580 minutes), and analyzed using a validated HPLC method. A reversed phase high performance liquid chromatographic method (RP-18) was used for the determination and quantification of plasma ciprofloxacin concentrations. The minimum quantifiable concentration of ciprofloxacin was 6 ng/ml (LOQ), the limit of detection (LOD) was 2 ng/ml, and calibration curves were linear over the range 0.01-8.0 µg/ml, with correlation coefficients >0.999. Both, the between-day coefficient of variation (interday RSD) and within-day coefficient of variation (intraday RSD) for quality-control samples were less than 5%. The pharmacokinetic values for ciprofloxacin were estimated by noncompartmental methods. When co-administered with the cabbage extract, Tmax for ciprofloxacin in plasma was reduced to the half; Cmax was increased by 1.5 times and AUC was 1.32 times higher. Results obtained indicated a potentiating effect of Brassica oleracea (Cabbage) on the ciprofloxacin which could be a result of the effect of glucosinolate and brassicasterol found in cabbage.